2007
DOI: 10.4012/dmj.26.414
|View full text |Cite
|
Sign up to set email alerts
|

Development of New Software as a Convenient Analysis Method for Dental Microradiography

Abstract: To the end of developing a convenient research tool to calculate the mineralization status of teeth in detail, a new program was developed using Visual Basic for Applications combined with Microsoft Excel 2004. To demonstrate the usefulness of this program, it was used to analyze tooth enamel mineralization after acid exposure. Transverse microradiography images (TMR) of specimens were digitalized with a charge-coupled device camera with a microscope (CCD camera) and a digital film scanner (FS). Subsequently, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 19 publications
(28 reference statements)
2
18
0
Order By: Relevance
“…In this study, enamel showed increases in the ΔIML, which indicated the amount of mineral loss, and the ΔLd, which indicated the depth of demineralization, over time; this tendency was similar to the that observed by Matsuda et al 18,19) . Of the three fissure sealants in the present study, IIILC yielded the lowest ΔIML and ΔLd values, followed by BS and TM; thus, inhibition of demineralization was highest in the IIILC group.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…In this study, enamel showed increases in the ΔIML, which indicated the amount of mineral loss, and the ΔLd, which indicated the depth of demineralization, over time; this tendency was similar to the that observed by Matsuda et al 18,19) . Of the three fissure sealants in the present study, IIILC yielded the lowest ΔIML and ΔLd values, followed by BS and TM; thus, inhibition of demineralization was highest in the IIILC group.…”
Section: Discussionsupporting
confidence: 74%
“…In accordance with the methods described by Matsuda et al 18,19) , TMR images were obtained using a CCD camera connected to a light microscope (BX50, Olympus, Tokyo, Japan) and general-purpose image processing software (WinROOF, Mitani Corporation, Fukui, Japan); the images were then digitized. Digitized images before pH-cycling and weekly images during pHcycling were overlapped with respect to a copper mesh that was overlaid on the specimen sections using Adobe Photoshop 8.0 (Adobe Systems Incorporated, San Jose, CA, USA).…”
Section: Assessment Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Evaluation of mineral loss and inhibition of demineralization TMR images of each section were examined before and after pH cycling according to a previously described procedure 37) . In brief, microradiographs were obtained in a soft X-ray system (CSM-2, Softex Corporation, Kanagawa, Japan) by using an aluminum step wedge and high-resolution photo plates (HRP-SN-2, Konica Minolta, Inc., Tokyo, Japan).…”
Section: Specimen Preparation and Automatic Ph Cycling This Experimenmentioning
confidence: 99%